2018
DOI: 10.1002/ppap.201800124
|View full text |Cite
|
Sign up to set email alerts
|

Controlling of reactive species in atmospheric Ar bubble discharge by adding N2/O2a

Abstract: An underwater Ar bubble discharge is excited by nanosecond pulsed power, and the effects of adding N2/O2 in Ar discharge on products are investigated. This work focus on regulating species concentration in plasma activated water (PAW), and then seeking specific concentrations for future application. The optical emission spectra (OES) and colorimetric chemical probes are used to diagnose and measure active species in plasma region or liquid phase. The H2O2 energy yield with Ar bubble can be up to 3.04 g kWh−1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
(43 reference statements)
1
16
0
Order By: Relevance
“…The related reactions are shown as R1–R3 in Table . Ground state H atoms are generated through the electron dissociation of H 2 O, and excited to H ( n = 3) by electron excitation processes (see R4 and R5) . The quenching processes of metastable N 2 (A) or N atoms by H 2 O are other pathways to generate H atom (see R6 and R7) .…”
Section: Resultsmentioning
confidence: 99%
“…The related reactions are shown as R1–R3 in Table . Ground state H atoms are generated through the electron dissociation of H 2 O, and excited to H ( n = 3) by electron excitation processes (see R4 and R5) . The quenching processes of metastable N 2 (A) or N atoms by H 2 O are other pathways to generate H atom (see R6 and R7) .…”
Section: Resultsmentioning
confidence: 99%
“…When a small amount of O 2 is added, O 2 mixed in plasma is dissociated O 2 and emitted O level from 3p 5 P to 3s 5 S by high‐energy free electrons. If O 2 is beyond a certain level, O 2 as an electronegative gas would strongly attract electrons in plasma, making more electrons attached by oxygen‐related species and trapped into the bulk area instead of forming the conductive current . As a result, the N 2 + (B) decreases with the increase of O 2 proportion due to quenching of electrons and metastable He atoms.…”
Section: Resultsmentioning
confidence: 99%
“…For pH measurement of liquid, a basic pH meter is used (PB‐10, Sartorius, Germany), and the initial pH values of deionized water and d ‐mannitol solution are 5.67 and 5.76, respectively. In previous works, we have investigated the variation of the concentrations of H 2 O 2 , NO3, and NO2 measured in time with Ar bubble discharge, and found that all above concentrations increase almost linearly. In this study, most of data are for a plasma treatment of 8 min, because the RONS concentrations are moderate for measurement in such condition.…”
Section: Methodsmentioning
confidence: 98%
“…Figure a shows the schematic diagram of the experiment setup of underwater bubble discharge. This setup is identical to that used in the experiments described previously . The discharge reactor consists of a quartz reaction vessel, a stainless steel high voltage (HV) needle electrode, and a copper coil ground electrode.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation